STUDY AND DEVELOPMENT OF AN ONLINE INTEGRATIVE COUNSELING PROGRAM TO ENHANCE STUDENTS’ CREATIVE PROBLEM-SOLVING ABILITIES IN ADDRESSING CYBERBULLYING AT SONGKHLA RAJABHAT UNIVERSITY - Rongpol, Maneenuch; Rongpol, Petch (Journal of MCU Nakhondhat, 2025)
This research is intended to 1) Study the creative problem-solving ability of university students in addressing cyberbullying 2) Develop an online integrative counseling program and 3) Examine the effects of the program. A quantitative research design was employed. In the first phase, the sample consisted of 400 students from Songkhla Rajabhat University selected through quota sampling. In the third phase, 30 students were randomly assigned into an experimental group (15 students) and a control group (15 students). The research instruments included a creative problem-solving ability assessment for cyberbullying and the online integrative counseling program, which was developed based on a creative problem-solving framework and implemented through 10 online sessions via Google Meet, each lasting 60 - 90 minutes.The program was evaluated for content validity by experts and piloted with a non-sample student group. Data were analyzed using mean, standard deviation, and t-tests. The results showed that students' overall creative problem-solving ability in dealing with cyberbullying was at a high level ( = 4.19, S.D. 0.46), with the highest mean score in the problem exploration component. Students in the experimental group scored significantly higher in creative problem-solving after the intervention than before, and also significantly higher than the control group at the .05 level of statistical significance. These findings indicate that the developed program was effective in enhancing students’ creative problem-solving abilities in response to cyberbullying situations.